Quality control of Photosystem II: reversible and irreversible protein aggregation decides the fate of Photosystem II under excessive illumination - Yamamoto, Yasusi; Hori, Haruka; Kai, Suguru; Ishikawa, Tomomi; Ohnishi, Atsuki; Tsumura, Nodoka; Morita, Noriko (Frontiers in Plant Science, 2013)
In response to excessive light, the thylakoid membranes of higher plant chloroplasts show dynamic changes including the degradation and reassembly of proteins, a change in the distribution of proteins, and large-scale structural changes such as unstacking of the grana. Here, we examined the aggregation of light-harvesting chlorophyll-protein complexes and Photosystem II core subunits of spinach thylakoid membranes under light stress with 77K chlorophyll fluorescence; aggregation of these proteins was found to proceed with increasing light intensity. Measurement of changes in the fluidity of thylakoid membranes with fluorescence polarization of diphenylhexatriene showed that membrane fluidity increased at a light intensity of 500–1,000 µmol photons m-2 s-1, and decreased at very high light intensity (1,500 µmol photons m-2 s-1). The aggregation of light-harvesting complexes at moderately high light intensity is known to be reversible, while that of Photosystem II core subunits at extremely high light intensity is irreversible. It is likely that the reversibility of protein aggregation is closely related to membrane fluidity: increases in fluidity should stimulate reversible protein aggregation, whereas irreversible protein aggregation might decrease membrane fluidity. When spinach leaves were pre-illuminated with moderately high light intensity, the qE component of non-photochemical quenching and the optimum quantum yield of Photosystem II increased, indicating that Photosystem II/ light-harvesting complexes rearranged in the thylakoid membranes to optimize Photosystem II activity. Transmission electron microscopy revealed that the thylakoids underwent partial unstacking under these light stress conditions. Thus, protein aggregation is involved in thylakoid dynamics and regulates photochemical reactions, thereby deciding the fate of Photosystem II.